2021
DOI: 10.1038/s41593-021-00800-0
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes mediate the effect of oxytocin in the central amygdala on neuronal activity and affective states in rodents

Abstract: Oxytocin (OT) orchestrates social and emotional behaviors through modulation of neural circuits. In the central amygdala (CeA), the release of OT modulates inhibitory circuits and, thereby, suppresses fear responses and decreases anxiety levels. Using astrocyte-specific gain and loss of function and pharmacological approaches, we demonstrate that a morphologically distinct subpopulation of astrocytes expresses OT receptors and mediates anxiolytic and positive reinforcement effects of OT in the CeA of mice and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
5
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(179 citation statements)
references
References 71 publications
8
156
5
10
Order By: Relevance
“…Somatodendritic release of AVP and OXT has important autocrine effects in MCNs and paracrine effects in nearby cells regulating a variety of functions such as the blood pressure 69 or the milk‐ejection reflex 70 . In addition, MCNs from the SON and PVN also send extra‐neurohypophyseal collateral projections to other brain areas contributing to central actions and affecting complex outputs, such as regulating pain perception, 71 affective/emotional states, 72,73 social behaviour, 74,75 fear, 76,77 and general anaesthesia and sleep 78 . It will be of great interest to identify individual MCN transcriptome signatures that mediate to these diverse physiological and behavioural roles.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Somatodendritic release of AVP and OXT has important autocrine effects in MCNs and paracrine effects in nearby cells regulating a variety of functions such as the blood pressure 69 or the milk‐ejection reflex 70 . In addition, MCNs from the SON and PVN also send extra‐neurohypophyseal collateral projections to other brain areas contributing to central actions and affecting complex outputs, such as regulating pain perception, 71 affective/emotional states, 72,73 social behaviour, 74,75 fear, 76,77 and general anaesthesia and sleep 78 . It will be of great interest to identify individual MCN transcriptome signatures that mediate to these diverse physiological and behavioural roles.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In various subcortical regions innervated by OT axons, the neuropeptide release is known to attenuate anxiety, fear, and physiological stress responses. Specifically, OT modulation of neural circuits in the central amygdala reduces contextual fear response (Knobloch et al, 2012;Hasan et al, 2019) and anxiety (Wahis et al, 2021), and in the lateral septum (LS) prevents social fear during lactation (Menon et al, 2018) as well as decreases aggression of female virgins (Oliveira et al, 2020). OT axons also reach the paraventricular nucleus of the thalamus (PVT) promoting maternal behavior (Knobloch et al, 2012;Cilz et al, 2018;Watarai et al, 2020).…”
Section: Brain-wide Ot Modulationmentioning
confidence: 99%
“…Although OTR neurons are present in the vast majority of forebrain regions, the anatomical and functional connectivity between them has only been explored by a few studies. While the dominating view is that OTR neurons generally represent GABAergic local interneurons (Marlin and Froemke, 2016 ), it is now known that principal glutamatergic neurons, as well as astrocytes, are also capable to express OTR (Mitre et al, 2016 ; Tan et al, 2019 ; Wahis et al, 2021 ).…”
Section: Do Otr Neurons In Distant Brain Regions Communicate To Each Other?mentioning
confidence: 99%
“…The amygdala mediates both conditioned and unconditioned memory of stressful events, so its activity increases during recollection. Studies using functional magnetic resonance imaging (fMRI) have shown an increase in spontaneous amygdala activity, as well as amygdala activity, when recalling traumatic events [229]. This explains why people suffering from PTSD have hippocampal atrophy without change in amygdala volume.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%